2014
DOI: 10.1055/s-0034-1396760
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Brachialis to the Anterior Interosseous Nerve as a Treatment Strategy for Cervical Spinal Cord Injury: Technical Note

Abstract: Study Design Technical report. Objective To provide a technical description of the transfer of the brachialis to the anterior interosseous nerve (AIN) for the treatment of tetraplegia after a cervical spinal cord injury (SCI). Methods In this technical report, the authors present a case illustration of an ideal surgical candidate for a brachialis-to-AIN transfer: a 21-year-old patient with a complete C7 spinal cord injury and failure of any hand motor recovery. The authors provide detailed description includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
3
13
0
4
Order By: Relevance
“…All patients with anterior/anteromedial FCs had denervation of the PT and/or FCR muscles observed on EDX and/or MRN. This finding is corroborated by previous reports associating the anterior/anteromedial region with motor nerve branches supplying the PT and FCR muscles . Maldonado et al documented frequent involvement of the PT and FCR muscles in clinically suspected “isolated” AIN palsy in 5 of 16 patients; in our study, 7 of 22 patients exhibited this phenomenon .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…All patients with anterior/anteromedial FCs had denervation of the PT and/or FCR muscles observed on EDX and/or MRN. This finding is corroborated by previous reports associating the anterior/anteromedial region with motor nerve branches supplying the PT and FCR muscles . Maldonado et al documented frequent involvement of the PT and FCR muscles in clinically suspected “isolated” AIN palsy in 5 of 16 patients; in our study, 7 of 22 patients exhibited this phenomenon .…”
Section: Discussionsupporting
confidence: 93%
“…We found posteriorly/posteromedially positioned FCs in 91% of site 1 patients, for which the mean distance was 4.7 cm proximal to the elbow joint line. This corresponds with the topographical location of the AIN fascicular bundle described in cadaveric and surgical studies . In a previous MRI study that reported fascicular abnormalities of the median nerve proper in patients with AINS, increased T2‐weighted signal was found in the posterolateral position of the median nerve (as opposed to the posterior/posteromedial position), and signal was maximal in intensity 14.6 cm proximal to the medial epicondyle .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The BCM branch has been transferred to the AIN fascicle in the arm to recover FPL and FDP function [147,177,178].…”
Section: Transfers For Spinal Cord Injured Patientsmentioning
confidence: 99%